Evaluation of Methiorep as a Substitute for Methionine in Broiler Diets - Salome, Itoe; Dafwang, I.I.; Bawa, G.S. (International Journal of Poultry Science, 2010)
A total of 225 day old broiler chicks were used to evaluate the use of Methiorep, a herbal Methionine product, as a substitute for synthetic Methionine in broiler diets. The experiment lasted from 0-4 weeks of age. The birds were randomly allocated to 5 dietary treatments in 3 replicates of 15 birds each, giving a total of 45 birds per treatment. The 5 dietary treatments comprised diet 1 which was devoid of supplementary Methionine and Methiorep, diet 2 had 0.25% Methionine, while diets 3-5 had graded levels of 0.25, 0.5 and 1% Methiorep respectively. All diets were isocaloric and isonitrogenous. The results showed that birds fed the Methionine supplemented diet performed significantly (p<0.05) better than other treatments in body weights, weight gains, feed intake, feed to gain and feed cost per kg gain. Dietary treatments had no significant effect on mortality rate. An analysis of the effect of graded levels of Methiorep on growth performance showed that Methiorep significantly improved growth performance up to 1% inclusion level but growth performance even at that level was inferior to that obtained on the 0.25% Methionine supplemented diet. It is concluded from this experiment that Methiorep is not an effective substitute for Methionine under the conditions of this study.